2017
DOI: 10.1111/ele.12821
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic attachment assembles plant–pollinator networks

Abstract: Species and interactions are being lost at alarming rates and it is imperative to understand how communities assemble if we have to prevent their collapse and restore lost interactions. Using an 8-year dataset comprising nearly 20 000 pollinator visitation records, we explore the assembly of plant-pollinator communities at native plant restoration sites in an agricultural landscape. We find that species occupy highly dynamic network positions through time, causing the assembly process to be punctuated by major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 68 publications
6
94
0
Order By: Relevance
“…The finding also highlights the role of common and abundant plants as reservoirs of symbiotic fungal diversity and thus contributors towards maintenance of ecosystem functions. Reliance of the symbiotic network on the most common hosts has earlier been demonstrated for aboveground mutualistic systems, such as plant–pollinator networks (Ponisio, Gaiarsa, & Kremen, ). Furthermore, Winfree, Williams, Dushoff, and Kremen () showed that network robustness in plant–pollinator systems is largely reliant on the most common plant species.…”
Section: Discussionmentioning
confidence: 88%
“…The finding also highlights the role of common and abundant plants as reservoirs of symbiotic fungal diversity and thus contributors towards maintenance of ecosystem functions. Reliance of the symbiotic network on the most common hosts has earlier been demonstrated for aboveground mutualistic systems, such as plant–pollinator networks (Ponisio, Gaiarsa, & Kremen, ). Furthermore, Winfree, Williams, Dushoff, and Kremen () showed that network robustness in plant–pollinator systems is largely reliant on the most common plant species.…”
Section: Discussionmentioning
confidence: 88%
“…having a specific degree distribution; Caldarelli, ), but deviate from these rules in small yet informative ways (specifically, about prey selection or predator avoidance). Opportunistic attachment and topological plasticity have been suggested as mechanisms that can move the system away from predictions based on power laws (Ramos‐Jiliberto et al, ; Ponisio, Gaiarsa & Kremen, ). We suggest that deviations from the power law be analysed as having intrinsic ecological meaning: why there are more, or fewer, species with a given frequency of interactions may reveal reasons for and/or constraints on particular species interactions.…”
Section: What Can We Learn With Ecological Network?mentioning
confidence: 99%
“…The previous subsection synthesised two frameworks to model population dynamics, one assuming static interactions (i.e., Lotka–Volterra type models) while the other allowing plastic interactions (i.e., consumer–resource model by Valdovinos et al .). This subsection synthesises studies that provide further understanding of the highly plastic nature of mutualistic interactions (CaraDonna et al ; Ponisio et al ).…”
Section: Towards Predicting the Dynamics Of Mutualistic Networkmentioning
confidence: 99%